Factors Influencing the Incidence of Diarrhea Among Under-Five Children in the Working Area of Candi Health Center, Sidoarjo - wigati, retno; Suprihatin, Kusmini; Maemonah, Siti; Hilmi M, M. Afif (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Diarrhea is still one of the main causes of morbidity and mortality in almost all geographic regions in the world, where all age groups can be attacked by diarrhea. Toddlers are an age group that is vulnerable to disease because their immune systems are still weak so they are easily attacked by bacterial, viral and parasitic infections. The purpose of this study was to determine the factors that influence the incidence of diarrhea in toddlers in the Candi Sidoarjo Health Center work area. This research method uses descriptive research involving 44 respondents. Data collection using observation sheets. The results of the examination showed that most respondents had a clean water source (68%), healthy toilets (66%), but there were still SPAL and trash bins that did not meet the requirements (48% and 52% respectively). In addition, although most mothers had good hand washing behavior (86%), diarrhea was still found. The conclusion of this study is that environmental and behavioral factors, especially those related to SPAL, waste management, and hand hygiene, play an important role in the incidence of diarrhea in toddlers. Education efforts and improvement of sanitation facilities are needed to reduce the prevalence of diarrhea in toddlers in the Candi Sidoarjo Health Center area.